IDENTIFIKASI DAMPAK AKSES JALAN TOL TERHADAP PENGGUNAAN LAHAN PERMUKIMAN DI KECAMATAN TEMBALANG - Hilmi Hilmansyah (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2023)
Construction of toll roads can be a generator in the development of Semarang City. It can be seen from the indications of an increase in population, and an increase in built-up land. A significant increase in the number of residents was in Tembalang District, namely 76,856 people. The expansion of built-up land is starting to be seen clearly in the city of Semarang, one of which is Bulusan Village and Tembalang Village which are located in Tembalang District. The development that took place in the Kelurahan was in the form of settlements (clean and slums) and trade and services and began to move rapidly since there was access to the Tembalang toll gate in the Tembalang Sub-District. In addition, there is a main driving factor for this increase, namely the difference between the Undip campus which is in the Tembalang Village. This study aims to identify how far the impact caused by the existence of toll gates in Tembalang Village from the spatial aspect in the form of residential land use (clean and slum). In achieving this goal, a spatial analysis of changes in land use was carried out from 1998 to 2018. Spatial urban development can be identified using land use data extracted from multitemporal Landsat imagery (Landsat 5 TM 1998, Landsat 7 ETM+ years, Landsat 7 ETM+ years 2003, Landsat 7 ETM+ in 2008, Landsat 7 ETM+ in 2013, Landsat 8 OLI in 2018). The results of the classification of land use show that the overall development of the city of Semarang leads to the east and south, the sub-districts with the number of built-up land growth are Tembalang, Banyumanik, Ngaliyan, Genuk, and Pedurungan. Then it was lowered again until the sub-district unit in Tembalang District saw an increase in built-up land in Tembalang and Bulusan Districts, both of which are the main gates using toll road access from the Tembalang Toll Gate.